Effect of contextual approach to improve competence of engineering design and manufacturing in vocational high school 2 Depok Sleman. (December 2020) - Ngadiyono, Y; Steven, S; Fikrie, A; Egiansyah, GYF
Abstract: The aim of this research was designed to determine the effect of contextual approaches on Manufacturing and Drawing Engineering competencies in class XII students of the Metal Fabrication and Manufacturing Engineering Vocational Engineering 2 Depok Sleman and improving the competency of the Manufacturing Image Engineering course by using the contextual approach of the XII grade students of the Metal Fabrication and Manufacturing Engineering expertise program at Vocational High School 2 Depok. This research is classroom action research. Data had collected in August 2019. Subjects were 29 students in class XII TFLM A. Data collection techniques used were observation, competency assessment, and documentation. The assessment technique applied in the study uses an evaluation based on the results of the student job sheet assignments. The results of this classroom action research are applying a contextual approach to improve student learning outcomes. The increase that can occur could be seen from the results of the 1st and 2nd cycle research. Increased value of cycle one by 3.4%. In the second cycle was 5.8%.